Broken bodies and healing communities: the challenge of HIV and AIDS in the South African context - Richardson, Neville (Cluster Publications, 2009)
"The book not only contributes to the academic debate about the pandemic but it provides a tool that needs to find a space in every household, as this would directly contribute to the government's as well as to the Religious Leaders' Awareness Campaign - that the HIV and AIDS pandemic exists and kills. Whilst the authors do not claim to have provided a medicinal cure for the disease, they do provide a source of encouragement to those broken bodies who are victims of the scourge. Well known scholars, some of them major names in South African theology, others drawn from the international scene, consider how the Bible, our ideas of Church, our practical theology, are all challenged and perhaps changed in the face of social realities, especially that of HIV and AIDS. Each of the contributors challenges us. Many of them break new ground. All of them raise questions which we need to face in obedience to God. What have been the effects of HIV and AIDS on some communities, and what have been the responses of others? Can those with better resources, both material and spiritual, offer help and healing and, in the process, become better communities themselves? How is the ambiguous response of the churches to be understood? In the absence of vaccine or cure, can healing nevertheless take place? Can suffering individuals, families and communities be helped to cope? These are questions no-one concerned with HIV and AIDS can afford to ignore"–Publisher's website.